TINJAUAN TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH OKNUM ANGGOTA TENTARA NASIONAL INDONESIA DI KOTA SAMARINDA - Try Sutrisno (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
Abstract       The problem in this study is how the authority and legal process against Narcotics acts by unscrupulous members of the TNI in Samarinda City as well as additional criminal dismissals from military service. Members of the TNI as perpetrators of narcotics crime other than subject to criminal imposition according to what is stipulated in Law Number 35 of 2009 concerning Narcotics may be subject to additional criminality in the form of dismissal from military service regulated in Article 6 letter b of KUHPM. The purpose of this paper is to explain the consideration of the Balikpapan I-07 Military Court judge in dropping an additional criminal dismissal from military service against members of the TNI as perpetrators of narcotics crimes and the possibility of imposing other types of criminal offenses against TNI members as narcotics offenders.In this thesis library and field research is conducted to obtain Primary data through interviews and secondary theoretical. From the results of the study it is known that the orders of superiors, military interests, the services of TNI members of narcotics criminals while in the military and the involvement of TNI members in acts of narcotics in narcotics cases are considered by military court judges in imposing additional criminal penalties. Additional types of criminal acts applied to members of the TNI that were proven to be involved in narcotics crimes were only in the form of dismissal from military service and there was no possibility of dropping other additional types of criminal offenses, because the dismissal of military service was considered comparable to criminal acts. The Army has issued Telegram Letter Number STR / 771/2018 dated July 9, 2018 concerning the prohibition of drug abuse and circulation for members of the Indonesian Armed Forces